Judicial deliberation as a condition for the standardization of jurisprudence in the Higher Courts: sustainable jurisdiction (Research, Society and Development, 2022)
The current Brazilian legal system is organized in such a way that jurists, especially in the Superior Courts, use their position of authority not to use the deliberative method in their decisions. Thus, there is the construction of precedents and enunciations that are limited to the opinion of the Justices, expressed in general formulas that will form the body of judicial precedents, conditioning the admission of special and extraordinary appeals, in the light of the provision of article 1.030, caput, of the CPC/15. The Courts weaken collective deliberation, to the extent that it authorizes the individual conduct of the ministers. Thus, in order to analyze the deliberative performance of the Courts, a bibliographic and jurisprudential survey was conducted, through which it was possible to understand that the deliberative method directly impacts the legal security of the Judiciary, since it is closely linked to the legitimacy of the decision-making power that is progressively conquered. However, the Higher Courts have not been deliberating, condemning the decision-making process to ruin and bringing about a problem of legitimacy of the institutions as judging collegiate.